Strategi Pengelolaan Wakaf Uang Sebagai Dana Abadi Masjid Dalam Perspektif Islam - Syahrir Akbar; Rehan Perdana Putra; Nayla Maulida Ellysia Rahma (Jurnal Penelitian Ilmiah INTAJ, 2025)
This research highlights the suboptimal management of cash waqf in Indonesia, where most returns are used for consumptive purposes, such as mosque operations. Cash waqf has greater potential when managed as a productive endowment fund to enhance community welfare. The study aims to analyze the potential and challenges of cash waqf management, propose strategies for its effective utilization as an endowment fund, and examine its alignment with Islamic principles. A qualitative descriptive method was employed, using literature reviews to explore the potential and issues surrounding cash waqf in Indonesia and the relevant Islamic principles. Observations were conducted to gather data on strategies for managing cash waqf as mosque endowment funds. Data were analyzed using descriptive and SWOT analysis. The study finds that cash waqf management benefits from strong regulatory support (strength) and the growth of the Islamic economic sector (opportunity). However, challenges such as limited management capacity (weakness) and economic instability (threat) persist. Based on SWOT analysis, four strategies are proposed: establishing mosque-based commercial ventures, empowering community economies, implementing Islamic financial management, and developing skilled human resources to manage waqf effectively. Islamic teachings emphasize the productive management of cash waqf to maximize its benefits for society. This aligns with Quranic guidance and the Prophet Muhammad’s (peace be upon him) teachings, which encourage the empowerment of mosques to improve the welfare of surrounding communities. By adopting these strategies, cash waqf can significantly contribute to sustainable community development.